A Review on Quantum Machine Learning and Quantum Cryptography - Mauricio Solar (Memoria Investigaciones en Ingeniería)
This article corresponds to an extensive review of Quantum Computers. We chose to consider topics relevant to quantum computing, such as machine learning, and the deepening of other issues related to cybersecurity. We introduce the reader to the basic concepts of quantum computing so that they can easily understand the terms mentioned in this review. We analyze different state of the art articles, and we give a summary of the contributions made. Finally, we conclude with the analysis of the bibliography, the research centers, the current state of the art, surprising results and conclusions.